Steroids and Brain, a Rising Bio-Medical Domain: a Perspective - Baulieu, Etienne-Emile (Frontiers in Endocrinology, 2018)
Some newly described steroid-related compounds, also found in the rest of the body, are formed and active in the Central Nervous System, particularly in the brain. Some are of pharmacological and physiopathological interest. We specifically report on two compounds, "MAP4343", a new neurosteroid very efficient antidepressant, and "FKBP52", a protein component of hetero-oligomeric steroid receptors that we found involved in cerebral function, including in Alzheimer's disease.